Enigmatic structures within salt walls of the Santos Basin—Part 1: Geometry and kinematics from 3D seismic reflection and well data - Jackson,CA-L; Jackson,MPA; Hudec,MR; Rodriguez,CR (Journal of Structural Geology, 2015)
Understanding intrasalt structure may elucidate the fundamental kinematics and, ultimately, the mechanics of diapir growth. However, there have been relatively few studies of the internal structure of salt diapirs outside the mining industry because their internal parts are only partly exposed in the field and poorly imaged on seismic reflection data. This study uses 3D seismic reflection and borehole data from the São Paulo Plateau, Santos Basin, offshore Brazil to document the variability in intrasalt structural style in natural salt diapirs. We document a range of intrasalt structures that record: (i) initial diapir rise; (ii) rise of lower mobile halite through an arched and thinned roof of denser, layered evaporites, and emplacement of an intrasalt sheet or canopy; (iii) formation of synclinal flaps kinematically linked to emplacement of the intrasalt allochthonous bodies; and (iv) diapir squeezing. Most salt walls contain simple internal anticlines. Only a few salt walls contain allochthonous bodies and breakout-related flaps. All of these are in an area having a density inversion within the autochthonous salt layer, such that upper, anhydrite-rich, layered evaporites are denser than lower, more halite-rich evaporites. We thus interpret that most diapirs rose through simple fold amplification of internal salt stratigraphy but that locally, where a density inversion existed in the autochthonous salt, Rayleigh-Taylor overturn within the growing diapir resulted in the ascent of less dense evaporites into the diapir crest by breaching the internal anticline. This resulted in emplacement of high-level intrsalt allochthonous sheets underlain by breakout-related flaps and steep salt-ascension zones or feeders. Although late-stage regional shortening undoubtedly occurred on the São Paulo Plateau during the Late Cretaceous, we suggest this was only partly responsible for the complex intrasalt deformation. Although based on the Santos Basin, our kinematic